1) Упростите выражнение: (3-5x)^2 - (3x-2)(5x+1); 6(a-2)(a-3)-4(a-3)^3;

0 рейтинг

1) Упростите выражнение:

(3-5x)^2 - (3x-2)(5x+1);

6(a-2)(a-3)-4(a-3)^3;


в разделе Алгебра
Всего ответов: 2
0 рейтинг

(3-5x)^2-(3x-2)(5x+1)=9-30x+25x^2-(15x^2+3x-10x-2)=9-30x+25x^2-15x^2+7x+2=10x^2-23x+11;

 

6(a-2)(a-3)-4(a-3)^3=(a-3)(6(a-2)-4(a-3)^2)=(a-3)(6a-12-4(a^2-6a+9))=(a-3)(6a-12-4a^2+24a-36)=(a-3)(-4a^2+30a-48)=-4a^3+30a^2-48a+12a^2-90a+154=-4a^3+42a^2-138a+154.

Начинающий
0 рейтинг

= 9-30Х+25Х²-15Х²+7Х+2=10Х²-23Х+11

6(А²-5А+6)-4(А³-9А²+27А-27)=6А²-30А+36-4А³+36А²-108А+108=-4А³+42А²-138А+144

Одаренный
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей